Probability and stochastic processes : a friendly introduction for electrical and computer engineers - Yates, Roy D.; Goodman, David J., 1939- (John Wiley & Sons, Inc., 2014)
"In Probability and Stochastic Processes: A Friendly Introduction for Electrical and Computer Engineers, readers are able to grasp the concepts of probability and stochastic processes, and apply these in professional engineering practice. The 3rd edition also includes quiz solutions within the appendix of the text. The resource presents concepts clearly as a sequence of building blocks identified as an axiom, definition or theorem. This approach allows for a better understanding of the material, which can be utilized in solving practical problems"--